2022
DOI: 10.5194/bg-19-4067-2022
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of methods to estimate gross primary production based on CO2 and COS flux measurements

Abstract: Abstract. Separating the components of ecosystem-scale carbon exchange is crucial in order to develop better models and future predictions of the terrestrial carbon cycle. However, there are several uncertainties and unknowns related to current photosynthesis estimates. In this study, we evaluate four different methods for estimating photosynthesis at a boreal forest at the ecosystem scale, of which two are based on carbon dioxide (CO2) flux measurements and two on carbonyl sulfide (COS) flux measurements. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…PAR availability, together with VPD, the major driver of short-term variability in LRU, typically decreases with canopy depth, and, since LRU is negatively related to PAR (e.g. Kooijmans et al, 2019;Kohonen et al, 2022), canopy-integrated LRU is expected to be larger than leaf-scale LRU at the top of the canopy (Sun et al, 2022). This in turn suggests the difference to the values by Maignan et al (2021) to diminish if their values were expressed at leaf scale and the top-of-the-canopy environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR availability, together with VPD, the major driver of short-term variability in LRU, typically decreases with canopy depth, and, since LRU is negatively related to PAR (e.g. Kooijmans et al, 2019;Kohonen et al, 2022), canopy-integrated LRU is expected to be larger than leaf-scale LRU at the top of the canopy (Sun et al, 2022). This in turn suggests the difference to the values by Maignan et al (2021) to diminish if their values were expressed at leaf scale and the top-of-the-canopy environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…While the magnitude and drivers of g s i are poorly understood, g s s and the C c i /C c a ratio are well known to vary over short timescales in response to diel changes in environmental drivers, as well as along large-scale bioclimatic gradients (Lloyd and Farquhar, 1994). With regard to the former, recent work by Kohonen et al (2022) and Sun et al (2022) demonstrated that contrasting leaf gas exchange theories are able to reproduce and explain the observed short-term response of LRU to key drivers such as incident PAR or the vapour pressure deficit (VPD).…”
Section: Introductionmentioning
confidence: 99%
“…(1) when NEE EC measurements are available, GPP is calculated as the difference between the NEE EC measurements and the respiration flux, which is calculated using a temperature function; or (2) when NEE EC measurements are not available, GPP is calculated using an equation that is based on the air temperature and light (photosynthetically active radiation, PAR). A more detailed description of these calculations is given by Kulmala et al (2019) and Kohonen et al (2022). By estimating ER r and ER a of this boreal forest, we created the opportunity to apply atmospheric O 2 measurements to separate NEE into GPP and TER (the O 2 method).…”
Section: Discussionmentioning
confidence: 99%
“…The eddy covariance COS flux data from Hyytiälä used for ecosystem COS flux assimilation and evaluation in this study are available in Kohonen, Tramontana, and Kolari (2022) via https://doi.org/10.5281/zenodo.6940750. The soil COS flux from chamber measurements at Hyytiälä used for assimilation are published in Sun et al.…”
Section: Data Availability Statementmentioning
confidence: 99%